A Simple Digital Semaphore Decoder Using DSP Processor - Syed Abu Bakar, Syed Abdul Rahman; Salleh, Sh-Hussain; Sha'ameri, Ahmad Zuri; Wei, L.C (2000)
This paper presents an innovative semaphore decoder using a DSP processor. The goal is to automate the interpretation of a semaphore code captured by a camera using basic image processing functions. Some of these functions involve image thresholding, image thinning, and image recognition. The system also introduced two new operations in its implementation and these were person detection and shoulder detection operations. This system has been implemented using actual image and has successfully decoded the semaphore language